(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the therapeutic efficacy and safety of electroacupuncture in patients with post-traumatic oculomotor nerve (cranial nerve III) palsy after etiological treatment. Methods: A before–after clinical intervention study was conducted on 30 patients with post-traumatic oculomotor nerve palsy. Outcome measures included clinical symptoms, the MRD1 index for ptosis assessment, levator palpebrae superioris muscle function, Traditional Medicine manifestations, and adverse events at baseline (D0) and after 20 days of treatment (D20). Results: After treatment, mean palpebral fissure width increased from 0.93 ± 1.53 mm to 7.60 ± 2.22 mm; levator muscle function score decreased from 3.93 ± 0.25 to 1.30 ± 0.47; and ptosis score decreased from 2.90 ± 0.31 to 0.83 ± 0.75 (p<0.001). Severe ptosis decreased from 90.0% to 0%, and 36.7% of patients achieved complete resolution of ptosis. Good and fair treatment outcomes accounted for 70.0% of cases. No adverse events were recorded. Conclusion: Electroacupuncture was effective in improving ptosis and restoring ocular motor function in patients with post-traumatic oculomotor nerve palsy, with a favorable safety profile.